Α-CC agostic structures and aggregation diversity in cyclopropyllithium derivatives. Issue 41 (21st April 2016) - Dufrois, Quentin; Vendier, Laure; Etienne, Michel
Abstract : A dinuclear cyclopropyllithium derivative exhibiting an α-CC agostic distortion in the solid state deaggregates to a mononuclear species in thf. Abstract : In the presence of thf or tmeda and depending on experimental conditions, 1-phenylcyclopropyllithium may be crystallised as either dinuclear or tetranuclear species both exhibiting α-CC agostic distortions towards tricoordinate lithium cations. In thf solution, deaggregation of the dinuclear complex takes place to yield a well-defined mononuclear species [Li(thf)3 ( c -CPhC2 H4 )].